A combined experimental and numerical study on droplet-impact induced breakup and ejection behaviors in vertical electric field. (10th August 2021) - Tian, Ye; Wang, Hong; Zhou, Xin; Deng, Qiyuan; Zhu, Xun; Chen, Rong; Ding, Yudong; Liao, Qiang
Highlights: The impact of a droplet on a charged substrate under electric field is investigated experimentally and numerically. Three different dynamic behaviors at the droplet vertex have been found. The mechanism of the droplet breakup behaviors is revealed. Abstract: Droplet impact on solid surface in the electric field is a fundamental process widely existing in our daily life and in engineering applications. Here, we investigated the dynamic behavior after droplet impact on the electrode plate in the electric field both experimentally and numerically. Particularly, the breakup or ejection behaviors were systematically studied. One key finding from the experiments is that the applied electric field can significantly affect the droplet stretching behavior, leading to two different breakup modes near the droplet top. We reproduced the two modes in the OpenFOAM simulation to reveal the intricate trade-off among the electrostatic force, surface tension and droplet gravity. Furthermore, the relationship between the impact Weber number, the applied electric field and the breakup modes was obtained. This work contributes to a thorough understanding of the droplet impact behavior and provides useful guidance for the development of modern droplet-related engineering applications.